Noncrystalline uric acid inhibits proteoglycan and glycosaminoglycan synthesis in distal tubular epithelial cells (MDCK) - Borges,F.T. (2010)
Hyperuricemia is associated with renal stones, not only consisting of uric acid (UrAc) but also of calcium oxalate (CaOx). Glycosaminoglycans (GAGs) are well-known inhibitors of growth and aggregation of CaOx crystals. We analyzed the effect of noncrystalline UrAc on GAG synthesis in tubular distal cells. MDCK (Madin-Darby canine kidney) cells were exposed to noncrystalline UrAc (80 µg/mL) for 24 h. GAGs were labeled metabolically and characterized by agarose gel electrophoresis. The expression of proteoglycans and cyclooxygenase 2 (COX-2) was assessed by real-time PCR. Necrosis, apoptosis and prostaglandin E2 (PGE2) were determined by acridine orange, HOESCHT 33346, and ELISA, respectively. CaOx crystal endocytosis was evaluated by flow cytometry. Noncrystalline UrAc significantly decreased the synthesis and secretion of heparan sulfate into the culture medium (UrAc: 2127 ± 377; control: 4447 ± 730 cpm) and decreased the expression of perlecan core protein (UrAc: 0.61 ± 0.13; control: 1.07 ± 0.16 arbitrary units), but not versican. Noncrystalline UrAc did not induce necrosis or apoptosis, but significantly increased COX-2 and PGE2 production. The effects of noncrystalline UrAc on GAG synthesis could not be attributed to inflammatory actions because lipopolysaccharide, as the positive control, did not have the same effect. CaOx was significantly endocytosed by MDCK cells, but this endocytosis was inhibited by exposure to noncrystalline UrAc (control: 674.6 ± 4.6, CaOx: 724.2 ± 4.2, and UrAc + CaOx: 688.6 ± 5.4 geometric mean), perhaps allowing interaction with CaOx crystals. Our results indicate that UrAc decreases GAG synthesis in MDCK cells and this effect could be related to the formation of UrAc and CaOx stones.